Clinical management of stage I pinkeye with concurrent pneumonic pasteurellosis in a goat: A case report (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This clinical case reports the occurrence of stage I pinkeye with concurrent pneumonic pasteurellosis in a goat. Materials and methods: A 2-year-old Jamnapari goat weighing 25 Kg was presented to the Universiti Veterinary Hospital, Universiti Putra Malaysia with primary complain of eye problem and inappetence.Results: Upon clinical examination, the most prominent abnormality observed was corneal opacity of the right eye with presence of ulceration on the corneal surface and chemosis of the right conjunctiva with excessive lacrimation. On auscultation, there was the presence of crackle lung sounds with bilateral mucopurulent nasal discharges. Samples from the ocular swab yielded a positive growth for Mycoplasma spp., while the nasal swab yielded a positive growth for Mannheimia haemolytica. The goat was diagnosed with stage I pinkeye with concurrent pneumonic pasteurellosis infection. Treatment was instituted with 400 mL of 0.9% NaCl administered intravenously once for rehydration. Flunixin meglumine 2.2 mg/kg bwt was given intramuscularly twice daily for three days as anti-inflammatory and analgesic. Oxytetracycline 20 mg/kg bwt was injected once intramuscularly as long acting broad spectrum antibiotic for treatment of pinkeye and pasteurellosis infections. Furthermore, terramycin eye ointment containing oxytetracycline HCl was also administered intraocularly twice daily for seven days as treatment for the Mycoplasma spp.Conclusion: The prognosis for this case was good as the goat were treated promptly and effectively.http://doi.org/10.5455/javar.2017.d228